ANALISIS PENGGUNAAN TEKNIK DASAR KONSELING TAHAP EKSPLORASI MASALAH PADA KONSELOR SMP KABUPATEN KUBU RAYA TAHUN AJARAN 2020/ 2021 - Yuline, Yuline; Halida, Halida; Putri, Amallia (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the ability of counselors to use basic counseling techniques in exploring the problems experienced by the counselee. The method used was descriptive survey research form. Data collection tools are questionnaires and interviews. Data analysis uses the percentage formula and rational analysis. The research population is 30 junior high school counselors who are members of the Musyawarah Guru Bimbingan dan Konseling Kubu Raya Regency. Determination of the sample using a total sampling technique. The general results of the study of counselors in the use of basic counseling techniques let the problem exploration stage obtained a score of 65% in the medium category. This means that the counselor has not been maximal in using basic counseling techniques at the problem exploration stage. When viewed from the sub-variables that get low scores, the skills to respond means that the counselor has not been able to use the skills to respond to content, respond to feelings and respond to meaning. The problem was that the counselor does not understand the basic techniques of counseling at the exploration stage of the problem, lacks self-development and was not accustomed to reading the latest literature. Suggestions need to collaborate with the Guidance and Counseling study program or other parties to hold training, seminars and workshop